Peran Motivasi Kepemimpinan Kepala Madrasah Tsanawiyah Ditinjau Dari Aspek Agama, Filosofis, Psikologis & Sosiologis Dalam Meningkatkan Kualitas Penyelenggaraan Pendidikan (Studi kasus pada Madrasah Tsanawiyah Swasta di Kecamatan Pebayuran Kabupaten Bekas: Peran Motivasi Kepemimpinan Kepala Madrasah Tsanawiyah Ditinjau Dari Aspek Agama, Filosofis, Psikologis & Sosiologis Dalam Meningkatkan Kualitas Penyelenggaraan Pendidikan (Studi kasus pada Madrasah Tsanawiyah Swasta di Kecamatan Pebayuran Kab - Ratih Komala; Heriyanto Heriyanto; Nur Apni Dwi Prastiwi (Pergunu Jawa Barat, 2021)
Abstract Leadership has a very close relationship with motivation, because the success of a leader in moving others to achieve the goals that have been set is very dependent on the authority and ability to create motivation. Without motivation in educational leadership, the educational process that has been stated in the National Education Standards will not run effectively, this can be seen in education under the auspices of the Ministry of Religion which includes RA, MI, MTS and MA which in its development is not as good as general education under the auspices of Ministry of Education, Culture, Research & Technology. The question that arises then, do education leaders in Indonesia have a strong character in building the motivation of all education actors to realize quality education? Thus, this study aims to identify the nature of the religious, philosophical, psychological and sociological leadership motivations of the madrasah principals in the Kec. Pebayuran Kab. Bekasi and its influence on the implementation of education. This study uses a literature study method and is accompanied by field studies with interview techniques and simple surveys to 10 Private Madrasah Tsanawiyah, Pabayuran District, Bekasi Regency. From the findings regarding the motivation to lead madrasah principals who tend to make awards as the main motivation in leading, but madrasah principals have been able to build motivation because generally madrasah principals have been able to create a conducive organizational climate by involving all parts of the organization to play an active role in achieving educational goals in madrasah. . The description of the leadership motivation of the Head of MTS has an impact on the implementation of education in Madrasahs which have the opportunity to continue to develop towards the provision of quality education that is able to compete with general education units so that they can jointly realize the goals of national education to educate the life of the Indonesian nation.